Emotional Intelligence and Attachment style Among Adolescents: A Correlational Study (Journal of Informatics Education and Research, 2024)
Emotional intelligence aids adolescents in the establishment of robust connections, enables them to reach sound judgments, and equips them to effectively navigate challenging circumstances. A perspective through which we can comprehend EQ is as an integral facet of possessing the ability to effectively interact with individuals, thereby enhancing our prospects of triumph in virtually every aspect of our existence. Comprehension and harmonious coexistence with fellow human beings not only contribute to our personal growth but also serve as a catalyst for attaining success across a wide spectrum of domains.Psychologists, in their rigorous exploration of human behavior, have identified a constellation of personality traits that are commonly referred to as the "dark triad." This triumvirate of psychological characteristics consists of a manipulative attitude, narcissism, and a startling lack of empathy. When confronted with the disconcerting possibility that one may have an evil child, it is only natural to seek clarity and understanding. However, discerning whether a child is truly malevolent or simply mischievous is no easy task. Fortunately, psychologists have developed a nuanced framework that allows them to distinguish between the merely naughty and the genuinely sinister. By meticulously examining the behavioral patterns and subtle indicators, these experts can shed light on the enigmatic signs that may suggest the presence of an evil child.